Β-glucan, "the knight of health sector": critical insights on physiochemical heterogeneities, action mechanisms and health implications. Issue 25 (1st September 2022) - Muthuramalingam, Karthika; Kim, Youngmee; Cho, Moonjae
Abstract: β-glucans, the class of biological response modifier has unceasing attention, not only for its immune stimulating but also for its role as prebiotics, modulator of physiological events etc. and is widely used in the treatment of cancer, diabetes, gastrointestinal disorders, cardiovascular diseases etc. However, β-glucan with different physiochemical properties is found to have discrete clinical functions and thus careful selection of the types of β-glucan plays pivotal role in providing significant and expected clinical outcome. Herein this review, we presented the factors responsible for diverse functional properties of β-glucan, their distinct mode of actions in regulating human health etc. Further, clinical aspects of different β-glucans toward the management of wound care, metabolic dysbiosis, fatty liver disorders and endurance training associated energy metabolism were compiled and exhibited in detail.